SCIENCE AND VALUES: MY DEBT TO ERNAN McMULLIN - Ruse, Michael (Zygon, 2012)
Ernan McMullin's 1982 presidential address to the Philosophy of Science Association dealt with the issue of science and values, arguing that although scientists are rightfully wary of the infiltration of cultural and social values, their work is guided by “epistemic values,” such as the drive for consistency and predictive fertility. McMullin argued that it is the pursuit of these epistemic values that drives nonepistemic values (like religious yearnings) from science. Using the case study of the fate of the nonepistemic value of progress in the history of evolutionary theorizing, I show that, vital though McMullin's thinking was for my own scholarship, in fact the study shows that the connections between epistemic and nonepistemic values in science are more complex than either of us supposed.